DISTANCE AND DOSAGE OF ORGANIC FERTILIZER INFLUENCE RESULTS OF EGG CABBAGE PLANT (BRASSICA OLERACEAE VAR. CAPITATA L) - KETUT TURAINI INDRA WINTEN; PANDE GEDE GUNAMANTA; ANAK AGUNG GEDE PUTRA (GANEC SWARA, 2019)
The low yield of cabbage is often associated with the low content of soil organic matter. The inappropriate planting distance also contributes to the low yield of the cabbage plant. The provision of organic fertilizer with the right dosage and setting the right spacing is also expected to increase soil fertility and ultimately increase results of cabbage plants.   This research was conducted in the field from April to July 2018 in Subak Gede Bungan Kapal, Tunjuk Village, Tabanan District, Tabanan Regency. Treatment was arranged in a factorial manner in a Randomized Block Design (RBD). Two treatments studied in this study were plant spacing (30 cm x 40 cm; 30 cm x 40 cm; 30 x 50 cm) and organic fertilizer (Petroganic) (0 t ha-1; 1 t ha-1; 2 t ha -1; 3 t ha-1). The treatment was repeated three times.   The results showed that the interaction between the treatment of spacing and the use of doses of organic fertilizer had no significant effect on all observed parameters.   The treatment of spacing has a significant effect on the diameter of the commercial crop -1, the weight of fresh stover ha-1, and has a very significant effect on the weight of crop ha-1, and the weight of commercial crop ha-1. The highest weight of commercial k-ha ha-1 was obtained at a plant spacing of 30 x 50 cm (J3) of 525.86 kg, significantly increasing by 74.80% compared to a spacing of 30 x 30 cm (J1) which was 299.12 kg.  The treatment of organic fertilizer dosage has a very significant effect on the weight of crop ha-1, weight of commercial crop ha-1, commercial crop diameter-1 but has no significant effect on the fresh weight of stover ha-1. The highest weight of commercial ha-1krop obtained at the dose of organic fertilizer 2 t ha-1 of 444.23 kg (P2) increased by 58.30% compared to the dose of 0 t ha-1 (P0) of 280.62 kg